2016
DOI: 10.5213/inj.1632796.398
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium Bromide Inhibits Inflammation and Pain by Suppressing Nitric Oxide Production and Enhancing Prostaglandin E<sub>2</sub> Synthesis in Endothelial Cells

Abstract: PurposeRocuronium bromide is a nondepolarizing neuromuscular blocking drug and has been used as an adjunct for relaxation or paralysis of the skeletal muscles, facilitation of endotracheal intubation, and improving surgical conditions during general anesthesia. However, intravenous injection of rocuronium bromide induces injection pain or withdrawal movement. The exact mechanism of rocuronium bromide-induced injection pain or withdrawal movement is not yet understood. We investigated whether rocuronium bromide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
11
2
Order By: Relevance
“… Alba et al (2006) demonstrated that iNOS expression was overexpressed under pain conditions, and iNOS inhibitors exerted anti-inflammatory effect. Therefore, expressions of COX-2 and iNOS are closely associated with the pathogenesis of inflammatory and neuropathic pain ( Baek et al, 2016 ). In the present study, COX-2 and iNOS expressions were increased by sciatic crushed nerve injury, indicating that injury to the sciatic nerve induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Alba et al (2006) demonstrated that iNOS expression was overexpressed under pain conditions, and iNOS inhibitors exerted anti-inflammatory effect. Therefore, expressions of COX-2 and iNOS are closely associated with the pathogenesis of inflammatory and neuropathic pain ( Baek et al, 2016 ). In the present study, COX-2 and iNOS expressions were increased by sciatic crushed nerve injury, indicating that injury to the sciatic nerve induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis for BDNF, TrkB, COX-2, iNOS were performed according to the previous method ( Baek et al, 2016 ; Park et al, 2017 ). Sciatic nerve tissue samples were homogenized in the lysis buffer and 200 μg the samples were centrifuged at 14,000 rpm at 20 min and supernatant collected for Western blot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the low potency of rocuronium to act as an antagonist on M 2 and M 3 receptors 23 makes it unlikely that clinically relevant effects may be observed, we cannot exclude that our results could have been influenced not only by the action of rocuronium on the muscle cell membrane, but also by extra-junctional receptor interaction. Furthermore has an influence of rocuronium on nitric oxide production been described 24 . The findings of this study by Baek et al .…”
Section: Discussionmentioning
confidence: 99%
“…One is “Current opinion on the role of neurogenesis in the therapeutic strategies for Alzheimer disease, Parkinson disease, and ischemic stroke; considering neuronal voiding function” [1] and the other is “Rocuronium bromide inhibits inflammation and pain by suppressing nitric oxide production and enhancing prostaglandin E2 synthesis in endothelial cells” [2]. …”
mentioning
confidence: 99%